2017
DOI: 10.1111/lang.12257
|View full text |Cite
|
Sign up to set email alerts
|

Beat Gestures and Syntactic Parsing: An ERP Study

Abstract: We tested the prosodic hypothesis that the temporal alignment of a speaker's beat gestures in a sentence influences syntactic parsing by driving the listener's attention. Participants chose between two possible interpretations of relative‐clause (RC) ambiguous sentences, while their electroencephalogram (EEG) was recorded. We manipulated the alignment of the beat within sentences where auditory prosody was removed. Behavioral performance showed no effect of beat placement on the sentences’ interpretation, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…On the other hand, the more positive-going P200 found in the readiness than pre-contemplation group suggests that the MI consistent words would have attracted more attention and higher dilemma conflict in the former than the latter group. These results are in line with those reported in a study conducted by Biau et al ( 2018 ) that the P200 amplitudes reflected the increased attention in processing the relevant information. Thus, for injured workers in a readiness stage, their engagements in the return to work process would have prepared them to perceive the semantic contents as more consistent than the pre-contemplating counterpart.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the more positive-going P200 found in the readiness than pre-contemplation group suggests that the MI consistent words would have attracted more attention and higher dilemma conflict in the former than the latter group. These results are in line with those reported in a study conducted by Biau et al ( 2018 ) that the P200 amplitudes reflected the increased attention in processing the relevant information. Thus, for injured workers in a readiness stage, their engagements in the return to work process would have prepared them to perceive the semantic contents as more consistent than the pre-contemplating counterpart.…”
Section: Discussionsupporting
confidence: 93%
“…Non-verbal information indeed translates the slow temporal structure of speech with a stable precedence (van Wassenhove et al, 2005 ; Chandrasekaran et al, 2009 ; Biau and Soto-Faraco, 2013 ; Biau et al, 2015 ): on the one hand, the syllabic rate is reflected by the corresponding mouth aperture and jaw constraints at theta frequency (Hickok and Poeppel, 2007 ; Giraud and Poeppel, 2012 ; Peelle and Davis, 2012 ). On the other hand, a speaker’s prosody (i.e., modulations of amplitude, duration, and pitch accents in the speech envelope) occurs at a slower 1–3 Hz delta rate and correlates also with body movements (Munhall et al, 2004 ; Krahmer and Swerts, 2007 ; Wagner et al, 2014 ; Biau et al, 2016 , 2017 ). Interestingly, speech-related motion perception has been shown to activate the speech network as well (Macaluso et al, 2004 ; Skipper, 2014 ; Biau et al, 2016 ).…”
Section: What’s the Role Of Lower Beta In Multimodal Speech: Discussimentioning
confidence: 99%
“…Two studies reported that presence of beat gestures induce less negative N400, similar to prosodic accentuation [43,44]. Other EEG studies, however, reported that beat gestures modulated brain responses in a later window (around 600 ms, interpreted as effects of beats on syntactic parsing [45] or on the integration of contextual information [46]).…”
Section: Introductionmentioning
confidence: 99%